Penatalaksanaan Pengendalian Infeksi Silang di Puskesmas Caringin Kecamatan Babakan Ciparay Kota Bandung Tahun 2022 (Poltekkes Kemenkes Bandung, 2023)
Dental equipment contaminated with the patient's blood and body fluids can lead to cross-infection. Dentists and dental and oral therapists are in direct contact with the patient's saliva and blood, so there is a high risk of causing disease transmission. Health workers in dental and oral health services in Indonesia have an obligation to carry out infection prevention and control (PPI) at work. This study aims to determine the Management of Cross Infection Control at Caringin Health Center, Babakan Ciparay District, Bandung City in 2022. The type of research used is descriptive research with a qualitative approach using observation, interviews, and filling out questionnaires. The results of the study on the Management of Cross Infection Control at the Caringin Health Center showed that the application of personal hygiene and the use of personal protective equipment and the handling of the treatment room were in accordance with the procedures. The handling of dental equipment has not been carried out 100% because it does not carry out instrument storage in accordance with infection prevention and control standards according to the Ministry of Health of the Republic of Indonesia in 2012, the contra angle head and water syringe are not covered by 70% alcoholic gauze, the lamp and instrument tray are not covered with alcoholic cotton 70%. Management of infection control has not been in accordance with the Standards for Prevention and Control of Cross Infections according to the Ministry of Health of the Republic of Indonesia in 2012.